Auto-vampirism in borderline personality disorder: A case report - Kazgan, Asli; Yildiz, Sevler; Korkmaz, Sevda; Atmaca, Murad (Klinik Psikiyatri Dergisi, 2021)
Auto-vampirism is a rare behavioral disorder in which a person sucks her/his own blood. The remarkable finding occurring in psychotic disorders such as schizophrenia but it can be seen in other psychiatric diseases. Personality disorders are also one of these diseases. Borderline personality disorder is a personality disorder characterized by imbalance in interpersonal relationships and mood, suicidal behavior, self-confusion and impulsivity. Impulsivity is one of the diagnostic criteria of borderline personality disorder. In this article we aimed to mention a patient, applying to us with complaints of self mutilation and after giving pleasurable blood sucking behaviour, diagnosed with borderline personality disorder accompanied by auto-vampirism and improvement in her clinical course with psychotherapy and psychopharmacological treatment method.
Borderline kişilik bozuklu?unda oto-vampirizm: Olgu sunumu
Keywords: Borderline personality disorder; auto-vampirism; self mutilation